Tax Strategies in Manufacturing: Profitability, Capital, and Inventory Impact: Strategi Pajak dalam Sektor Manufaktur: Dampak Profitabilitas, Intensitas Modal, dan Intensitas Inventaris - Muflikhatul Asrofiyah; Herman Ernandi (Academia Open, 2022)
This study examines the impact of profitability, capital intensity, and inventory intensity on tax avoidance and tax planning in the manufacturing sector, specifically focusing on industrial and consumer goods companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The research employs quantitative methods and utilizes primary data, collected based on predetermined criteria, for statistical analysis. The sample consists of 42 purposively selected companies from a population of 123 manufacturing firms. Multiple linear regression analysis using SPSS version 25 is employed to analyze the data. The findings reveal that profitability and capital intensity do not significantly influence tax avoidance, while inventory intensity does. Similarly, profitability and capital intensity do not significantly affect tax planning, whereas inventory intensity does. These results highlight the importance of inventory management and provide insights for manufacturing companies in formulating effective tax strategies to enhance financial performance and compliance with tax regulations. Highlights: The study investigates the impact of profitability, capital intensity, and inventory intensity on tax avoidance and tax planning in the manufacturing sector. Multiple linear regression analysis using SPSS version 25 is employed for statistical analysis. The findings reveal that inventory intensity has a significant effect on both tax avoidance and tax planning, while profitability and capital intensity do not demonstrate significant influences on either. Keywords: Tax Avoidance, Tax Planning, Profitability, Capital Intensity, Inventory Intensity